Overexpression of the Peach Transcription Factor Early Bud-Break 1 Leads to More Branches in Poplar - Zhao, Xuehui; Wen, Binbin; Li, Chen; Tan, Qiuping; Liu, Li; Chen, Xiude; Li, Ling; Fu, Xiling (Frontiers in Plant Science, 2021)
Shoot branching is an important adaptive trait that determines plant architecture. In our previous study, the EBB1 gene in peach (Prunus persica var. nectarina) cultivar Zhongyou 4 was transformed into poplar (Populus trichocarpa). PpEBB1-oe poplar showed more branched phenotype. To understand the potential mechanisms underlying EBB1-mediated branching, transcriptomic and proteomics analyses were used. The results showed that a large number of DEGs/DEPs associated with light response, sugars, brassinosteroids and nitrogen metabolism were significantly enriched in PpEBB1-oe poplar. In addition, contents of sugars, brassinosteroids and amino acids were measured. Results showed that PpEBB1 significantly promoted the accumulation of fructose, glucose, sucrose, trehalose and starch. Contents of BL, CS and 6-deoxoCS were all significantly changed with overexpressing PpEBB1. Various types of amino acids were measured and four of them were significantly improved in PpEBB1-oe poplar, including Asp, Arg, Cys and Trp. Taken together, shoot branching is a process controlled by a complex regulatory network, and PpEBB1 may play important roles in this process through the coordinating multiple metabolic pathways involved in shoot branching including light reponse, phytohormones, sugars, and nitrogen.